Limb girdle muscular dystrophy 23 caused by compound heterozygous mutations of LAMA2 gene - Xu, Yuqing; Zhu, Linyan; Qian, Yeqing; Dong, Minyue (Frontiers in Pediatrics, 2023)
Mutations of LAMA2 gene are associated with congenital muscular dystrophy (CMD). The LAMA2-related CMD mainly consists of two diseases, merosin deficient congenital muscular dystrophies type 1A(MDC1A）and limb girdle muscular dystrophy 23 (LGMD23). LGMD23 is characterized by slowly progressive proximal muscle weakness, which primarily affects the lower limbs and results in gait difficulties. Additional clinical features include increased serum creatine kinase, abnormal electromyography with or without white matter abnormalities on brain imaging. Herein, compound heterozygous mutations of LAMA2: c.1693C>T (p. Q565*) (maternally inherited) and c.9212-6T>G (paternally inherited) were identified by whole exome sequencing in a Chinese girl diagnosed as LGMD23. The mutation c.1693C>T (p. Q565*) was classified as pathogenic while c.9212-6T>G was classified as the variant of uncertain significance according to American College of Medical Genetics and Genomics (ACMG) guidelines. To investigate the pathogenicity of LAMA2: c.9212-6T>G, RT-PCR was conducted with peripheral blood. TA clone and sequencing were then carried out with the PCR products. An insertion of 40-bp intronic sequence (intron 64) was found in the transcripts of the proband and her father, which resulted in a frameshift and premature truncation codon of the LAMA2. In particular, the variant truncated the LamG domain of the LAMA2. Our findings expand the phenotypic and variant spectrum of the LAMA2-related CMD.